CLINICAL ANALYSIS AND OPTIMIZATION OF POST-REMISSION THERAPY FOR ACUTE MYELOID LEUKEMIA PATIENTS WITH MINIMAL RESIDUAL DISEASE AS DETERMINED BY FLOW CYTOMETRY - Daichi Inoue; Hayato Maruoka; Takayuki Takahashi (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Although several prognostic indicators of de novo acute myeloid leukemia (AML) patients have been identified, the clinical significance of minimal residual disease (MRD) needs to be evaluated further in Japanese adult patients. Methods: Using three color flow cytometry, we identified leukemia-associated phenotypes (LAP) in bone marrow specimens at diagnosis and assessed the relationship between clinical outcomes and the presence of marrow MRD in 33 patients who achieved a morphologic complete remission (CR) and were followed after CR. Results: Of 33 consecutive patients, we detected MRD in 20 patients after achieving CR (Group A) and did not in 13 patients (Group B), with 2-year overall survival (OS) rates of 49.0% and 84.6%, respectively (P =.0317), and relapse-free survival (RFS) rates of 13.7% and 91.7%, respectively (P=.0010). By multivariate analysis, MRD-positivity at post-induction was found to be associated with a shorter duration of RFS (P=.0042). Notably, we achieved MRD negativity in only 2 patients (10%) of Group A in spite of subsequent intensive consolidation therapies and found that the fluctuation of the MRD level during consolidation therapies was not a significant prognostic factor. Four patients in Group A underwent allogeneic hematopoietic stem-cell transplantation (HSCT) when in the CR state and did not experience relapse at a median follow-up period of 20.5 months after HSCT. Conclusions: MRD is critical for predicting de novo AML outcomes. Most MRD-positive patients cannot achieve MRD negativity with conventional chemotherapy. Thus, HSCT may be the primary therapeutic option for these patients.